PERILAKU LENTUR BALOK-L BETON BERTULANG BERLUBANG DITINJAU SECARA EKSPERIMEN DAN ANALISIS NUMERIK MEMAKAI SOFTWARE GID-ATENA - Kori Effendi, Mahmud (Semarang State University, 2010)
Abstract:.Investigation on behavior of openings-beam reinforced concrete with the variation type of sided is conducted experimentally and numerical analytically using GID-ATENA software. Used specimens were reinforced concrete L-shaped beam designed with ultimate load 2600 N and having tension reinforcement 2D13 with roll and hinge support. Beam had 2 m span, 150 mm web width, 250 mm high, effective 317 mm width and slab 100 mm thick,. To differentiate behavior of openings, a specimen without openings ( BLK01), a specimen with openings 100 mm x 100 mm ( BLKLB01), a specimen with openings 200 mm x 100 mm ( BLKLB02) were made. An opening was 150 mm from right support. Pure moment was done with load 650 mm from support. To compare experiment, 3D model GID-ATENA was analyzed. The material model of concrete was CCCOMBINEDMATERIAL and CC1DELASTLSOTROPIC for reinforcement. This analysis used geometric and material non linear analyses.Result of GID-ATENA analysis indicate that the first crack load were less than 42-62 %, ultimate load were less than 33-47%, mid-span displacement at first crack load were less than 55-86%, and mid-span displacement at ultimate load were less than 45-70% compared to the experiment result. First crack pattern of BLK01 occured in the mid-span while BLKLB01 and BLKLB02 occurred below the hole. Result of analysis GID-ATENA get the different result of its first crack pattern. Keywords: openings-beam, L-shaped beam, GID-ATENA Abstrak: Pengamatan perilaku balok beton bertulang berlubang di badan dengan variasi entuk persegi panjang dilakukan secara eksperimen. Benda uji yang digunakan adalah balok L beton bertulang yang dirancang dengan beban 2600 N dan menghasilkan tulangan tunggal 2D13 dengan tumpuan sendi dan rol. Balok mempunyai bentang 2 m, lebar web 150 mm, tinggi 250 mm, tebal slab 100 mm, lebar efektif 317 mm. Untuk mengetahui perilaku lubang di badan maka dibuat benda uji balok tanpa lubang (BLK01), balok dengan lubang 100 mm x 100 mm (BLKLB01), balok dengan lubang 200 mm x 100 mm (BLKLB02). Jarak lubang 150 mm dari tumpuan kanan. Masing2 benda uji 1 buah. Untuk mengetahui kapasitas beban maksimum yang ditahan balok, balok dites lentur murni dengan jarak beban titik 650 mm dari tumpuan. Hasil analisis GID-ATENA menunjukkan bahwa beban retak balok pertama lebih kecil 42-62 %, beban ultimit balok lebih kecil 33-47%, lendutan tengah bentang pada beban retak pertama lebih kecil 55-86%, dan lendutan tengah bentang pada beban ultimit lebih kecil 45-70% terhadap hasil eksperimen. Pola retak pertama balok BLK01 terjadi di tengah bentang sedangkan BLKLB01 dan BLKLB02 terjadi di bawah lubang. Hasil analisis GID-ATENA mendapatkan hasil yang berbeda pola retak pertamanya. Kata Kunci: Balok lubang, Balok L, GID-ATENA